2022
DOI: 10.3389/fphar.2022.902259
|View full text |Cite
|
Sign up to set email alerts
|

NEU1—A Unique Therapeutic Target for Alzheimer’s Disease

Abstract: Neuraminidase 1 (NEU1) is considered to be the most abundant and ubiquitous mammalian enzyme, with a broad tissue distribution. It plays a crucial role in a variety of cellular mechanisms. The deficiency of NEU1 has been implicated in various pathological manifestations of sialidosis and neurodegeneration. Thus, it is a novel therapeutic target for neurodegenerative changes in the Alzheimer’s brain. However, to manipulate NEU1 as a therapeutic target, it is imperative to understand that, although NEU1 is commo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 98 publications
(212 reference statements)
0
1
0
Order By: Relevance
“…Likewise, alterations in sialylation patterns have been observed in both neurological disorders and the microglia's inflammatory response (Minami et al, 2017;Annunziata et al, 2013). Khan et al (2021) found that Neu1 deficiency can cause an amyloidogenic process similar to Alzheimer's Disease (AD) in mice (Khan et al, 2021;Khan and Sergi, 2022). In this disease, Neu1 desialylates macrophage and dendritic cell surface receptors and activates phagocytosis.…”
Section: Sialidases In Neurological and Metabolic Disordersmentioning
confidence: 99%
“…Likewise, alterations in sialylation patterns have been observed in both neurological disorders and the microglia's inflammatory response (Minami et al, 2017;Annunziata et al, 2013). Khan et al (2021) found that Neu1 deficiency can cause an amyloidogenic process similar to Alzheimer's Disease (AD) in mice (Khan et al, 2021;Khan and Sergi, 2022). In this disease, Neu1 desialylates macrophage and dendritic cell surface receptors and activates phagocytosis.…”
Section: Sialidases In Neurological and Metabolic Disordersmentioning
confidence: 99%
“…Fourth, we also reported that neuraminidases activation resulted in accumulation of circulating N -acetyl-neuraminic acid, a signaling metabolite that can trigger RhoA and Cdc42-dependent myocardial injury 21 . On account of their various functions, mammalian neuraminidases have been shown to play an emerging role in several human diseases, including autoimmune 22 , 23 , cardiovascular diseases 20 , 24 , 25 cancers 26 , neurodegenerative disorders 27 , and lung diseases 28 , 29 . Design of the specific inhibitors targeting neuraminidases have the potential to treat these diseases 30 , 31 .…”
Section: Introductionmentioning
confidence: 99%